The Impact of Perception, Business Experience, and Scale on the Use of Accounting Information in Micro, Small, and Medium Enterprises: The Influence of Perceptions of Micro, Small and Medium Enterprises on Accounting, Business Experience, and Bussiness Scale on the Use of Accounting Information - Nabilla Putri; Hadiah Fitriyah (Universitas Muhammadiyah Sidoarjo, 2024)
This study aimed to investigate the impact of perception, business experience, and scale on the use of accounting information in micro, small, and medium enterprises (MSMEs). The study used a quantitative approach with a sample of 100 MSMEs in Sukodono District, Sidoarjo Regency. The data were collected using a Likert scale questionnaire and analyzed using multiple linear regression analysis with SPSS 26. The results showed that (1) the perception of MSMEs about accounting had a significant effect on the use of accounting information, (2) business experience did not have a significant effect on the use of accounting information, and (3) the scale of the business did not have a significant effect on the use of accounting information. This study implies that MSMEs should pay attention to their perception of accounting to improve the use of accounting information in their business operations.Highlights: Perception of accounting has a significant effect on the use of accounting information in MSMEs. Business experience and scale do not have a significant effect on the use of accounting information in MSMEs. MSMEs should pay attention to their perception of accounting to improve the use of accounting information in their business operations. Keywords: perception, business experience, scale, accounting information, MSMEs